Belonging and the Self as Enterprise: Place, Relationships and the Formation of Occupation‐Based Identities. Issue 2 (4th December 2019) - Cook, Julia; Woodman, Dan
Abstract: Research considering young adults' experiences of place is characterised by two focal points: the relationship between place, education and employment; and immaterial aspects of place such as experiences of belonging and relationality. Previous research has worked across these focal points considering, for instance, how symbolic and immaterial factors and social ties can inform mobility choices and experiences. We extend this work by drawing on longitudinal qualitative data to show three ways that place attachment can be a part of the formation of contemporary occupation‐based identities. Using the concept of the self as enterprise (Kelly 2013), we mark out this development as part of a broader generational shift in occupational identities. We ultimately find that some young adults can remain in or return to meaningful rural and regional places by developing an occupational identity or 'personal brand' informed by changing occupational demands and enabled by social ties linked to specific places.